2005
DOI: 10.1007/s00122-005-2019-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance and breeding values for resistance to a wind-borne disease [Sphaerotheca macularis (Wallr. ex Fr.)] in strawberry (Fragaria × ananassa Duch.) estimated by exploring mixed and spatial models and pedigree information

Abstract: A mixed model approach was used to estimate variance components and heritabilities for resistance to powdery mildew, a wind-borne disease in strawberry. In order to improve precision in the statistical computations, spatial error control effects were included to account for systematic environmental variations in the large field trials. Pedigree information was included where feasible. Seedling families obtained from an incomplete 63-by-63 diallel cross were grown at six locations and scored subjectively for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…We found multiple QTL of small to moderate effect control disease resistance in both populations. Likewise, previous studies have found multiple small effect QTL which contribute to powdery mildew resistance in strawberry indicating quantitative resistance with both additive and non-additive genetic components (Simpson 1987; Nelson et al 1995; Davik and Honne 2005). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found multiple QTL of small to moderate effect control disease resistance in both populations. Likewise, previous studies have found multiple small effect QTL which contribute to powdery mildew resistance in strawberry indicating quantitative resistance with both additive and non-additive genetic components (Simpson 1987; Nelson et al 1995; Davik and Honne 2005). …”
Section: Discussionmentioning
confidence: 86%
“…It was hypothesised that this may be attributed to low genetic variability in strawberry germplasm or low variation between mildew isolates (Xu et al 2008b). However, there is some evidence to suggest heterogeneity between populations of P. aphanis , namely the evolution of fungicide resistance (Sombardier et al 2010) and the resistance breaking in the cultivar Korona, likely due to the evolution of more virulent strains (Davik and Honne 2005). Reports of the production of ascospores in UK infections indicate the presence of a sexual cycle within powdery mildew (Xu et al 2008a), and high recombination associated with this life cycle typically leads to greater genetic diversity than observed in asexual reproduction (Barrett et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Purba et al (2001) applied Bernardo's approach to predict performance of oilpalm (Elaeis guineensis) hybrids. Davik and Honne (2005) modeled GCA effects in a diallel experiment with strawberry (Fragaria spp.) using the A matrix ''under the usual assumptions of a large random mating parental population'', while SCA effects were assumed to be uncorrelated.…”
Section: Cross-fertilized Cropsmentioning
confidence: 99%
“…By contrast, Simpson (1987), while evaluating the progeny of remontant varieties of strawberry had proven that additive effects are dominant in the inheritance of the trait of powdery mildew susceptibility. Likewise, Davik and Honne (2005), MacLachlan (1978), and McNicol and Gooding (1979) had proposed a quantitative model of the inheritance of resistance to powdery mildew, in which the additive variance (GCA) is of a far greater importance, while the non-additive (SCA) effects, although also significant, are less important. In a study by Davik and Honne (2005), specific combining ability variance represented only 10-13 % of the total combining ability.…”
Section: Discussionmentioning
confidence: 97%